Role of extracellular matrix protein peroxidasin (PXDN) in breast cancer progression - Aldís María Antonsdóttir 1998- (2023)
Breast cancer is the most common cancer among females with 242 diagnoses on average every year in Iceland. The interactions between epithelial cells in the mammary gland and the surrounding stroma in the extracellular matrix are crucial for normal function. Basement membrane is a big part of that stability with collagen IV as the leading structural protein. Peroxidasin (PXDN) is an extracellular matrix protein that promotes crosslinking of collagen IV molecules in the basement membrane. It is therefore likely that PXDN is an important protein for stability of the organ’s structure. However, mice with PXDN depletions on both alleles were born seemingly normal in all ways, but with eye malfunction, demonstrating that crosslinking of collagen IV must be possible without PXDN. Nevertheless, PXDN has been linked to several cancers, for instance melanoma and ovarian cancer. The aim of this study is to investigate whether invasive properties of breast cancer cells are affected by manipulation of PXDN levels. Knockdown of PXDN in breast cancer cell line (HCC1143) didn’t have any changes is proliferation, migration, or invasion. Overexpression of PXDN in the same cell line did show some changes regarding to invasion and drug cancer sensitivity. Within normal breast progenitor cell line (D492) that had PXDN overexpression, there were not many changes in phenotype, apart from raised EMT markers and an indication that PXDN impacts migration. We also overexpressed PXDN together with the HER2 oncogene in D492 and noticed increased invasion properties with double overexpression. RNA sequencing data showed that D492-PXDN/HER2 is more similar to D492-empty/HER2 than D492- PXDN/empty. Previous studies with PXDN and HER2 overexpression in D492 cells show not all the same results and therefore it can be concluded that lentiviral transduction may have impact on phenotypic changes in overexpressed cells. Taken together, these results indicate that the extracellular matrix protein PXDN has minor or no effect on breast cancer ...